The Effect of Anti-Immigrant Discourses on Voter Behaviors in the Context of Critical Discourse Analysis: The Case of the Italian League Party - Salih Turgay (Güvenlik Stratejileri Dergisi, 2023)
After the end of the Cold War, the increasing migration movements have deeply affected Italy, which is on the most active migration route between Africa and Europe. Intensive migration movements towards Italy, which is both a transit and a destination country, have been more politicized day by day and become one of the most controversial issues on the political plane. While regionalism was at the center of the political discourse of the farright League Party, which has managed to become an important actor in the Italian political system since its establishment until the 2000s, anti-immigration began to characterize the party’s general political line and ideological stance as of the 2000s. This study discusses the metaphors through which the League Party carries out its anti-immigration discourses and the reflections of these discourses on the Italian general elections and European Parliament elections. It tries to make sense of the metaphors that the actors of the League Party brought to the forefront and the relationship between their communication strategies, their election posters, and these metaphors by using the critical discourse analysis method. In this sense, the main purpose of the study is to reveal whether the anti-immigrant discourse of the actors of the League Party is a variable that affects the party’s votes. According to the findings of the study, anti-migration discourse reflects positively on the election results in times when immigrants occupy the public agenda due to factors such as crime rates and cultural differences or when mass migration movements increase the sensitivity level of society. However, the study also shows that anti-immigration rhetoric does not perform the expected effect on voters’ behaviour in times when economic and social problems diverge.